Effects of ABC transporter polymorphism on the pharmacokinetics of pentoxifylline and its active metabolites in healthy Chinese subjects - Lingfang Guo; Xue Sun; Bo Qiu; Wanjun Bai; Yabin Du; Haojing Song (European Journal of Clinical Pharmacology, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Heterogeneous responses of soil nitrous oxide emissions to nitrogen addition: A global meta-analysis - Peng Guo; Jingwen Diao; Tian Zuo; Han Zhao; Dongyan Kong; Lingfang Yang; Mengyu Miao (CATENA, 2025)

Colonization characteristics and dynamic transition of archaea communities on polyethylene and polypropylene microplastics in the sediments of mangrove ecosystems - Qiong Wang; Gang Zheng; Lingfang Ni; Heng Wang; Weiye Li; Peng Guo; Yi Wang; Daoqiong Zheng; Jiaping Wu; Dongdong Zhang (Journal of Hazardous Materials, 2024)

Learning dense gas-solids flows with physics-encoded neural network model - Xiaolin Guo; Chenshu Hu; Yuyang Dai; Hongbo Xu; Lingfang Zeng (Chemical Engineering Journal, 2024)

Differences in Characteristics of Sample Sites Explain Variable Responses of Soil Microbial Biomass to Nitrogen Addition: A Meta-Analysis - Peng Guo; Dongyan Kong; Lingfang Yang; Xiao Sun (Ecosystems, 2023)

Improved simultaneous nitrification–denitrification in fixed-bed baffled bioreactors treating mariculture wastewater: Performance and microbial community behaviors - Peng Guo; Qiong Wang; Lingfang Ni; Silong Xu; Daoqiong Zheng; Yi Wang; Fang Cai; Mingyu Cui; Zhiwei Zheng; Xiuqing Gao; Dongdong Zhang (Bioresource Technology, 2023)

Differential effects of ammonium and nitrate addition on soil microbial biomass, enzymatic activities, and organic carbon in a temperate forest in North China - Peng Guo; Lingfang Yang; Dongyan Kong; Han Zhao (Plant and Soil, 2022)

Altered brain activity in the bilateral frontal cortices and neural correlation with cognitive impairment in schizophrenia - Lingfang Yu; Lei Guo; Xinyu Fang; Fuyin Yang; Yan Chen; Yewei Wang; Dandan Wang; Zenan Wu; Ruimei Liu; Xing Tian; Chen Zhang (Brain Imaging and Behavior, 2022)

The genome sequence of Brassica campestris chrysovirus 1, a novel putative plant-infecting tripartite chrysovirus - Jun Zhang; Zhonghao Zhao; Rong Hu; Lingfang Guo; Limin Zheng; Zhenguo Du; Zujian Wu; Shouguo Fang; Songbai Zhang; Yong Liu (Archives of Virology, 2017)

Complete sequence of a double-stranded RNA from the phytopathogenic fungus Erysiphe cichoracearum that might represent a novel endornavirus - Zhenguo Du; Wenzhong Lin; Ping Qiu; Xiaojuan Liu; Lingfang Guo; Kangcheng Wu; Songbai Zhang; Zujian Wu (Archives of Virology, 2016)

Identification and molecular characterization of Panax notoginseng virus A, which may represent an undescribed novel species of the genus Totivirus, family Totiviridae - Lingfang Guo; Xin Yang; Wei Wu; Guanlin Tan; Shouguo Fang; Songbai Zhang; Fan Li (Archives of Virology, 2016)

The effects of lanthanum chloride on proliferation and apoptosis of cervical cancer cells: involvement of let-7a and miR-34a microRNAs - Lingfang Yu; Jieqi Xiong; Ling Guo; Lifang Miao; Sisun Liu; Fei Guo (BioMetals, 2015)